Contribution of Work Environment on Employee Retention in the Financial Sector of Nepal - Prakash Bahadur Chand (PT Mattawang Mediatama Solution, 2026)
Employee retention is a critical challenge for organizations globally, affecting operational efficiency, morale, and long-term success. This study investigates the impact of the work environment encompassing both physical (workspace layout, safety) and psychological factors (organizational culture, leadership and management practices) on employee retention in Nepal’s financial sector. By identifying key environmental determinants, the research aims to provide actionable insights for organizations seeking to enhance retention strategies. This study adopts a descriptive and analytical research design, employing a purposive sampling technique to collect data from 385 respondents in Nepal’s financial sector. A structured, closed-ended questionnaire using a five-point Likert scale was administered to assess employee perceptions of workspace layout, safety, organizational culture, and leadership. Data analysis was conducted using SPSS to evaluate the relationship between work environment factors and retention. Workspace layout, organizational culture, and leadership & management significantly enhance employee retention. Employees reported high satisfaction with leadership and management, followed by workspace layout and organizational culture, underscoring their pivotal role in retention. While safety remains important, its direct impact on retention is relatively minimal, suggesting room for improvement. This study adds to existing literature by examining employee retention in Nepal’s financial sector a relatively unexplored context—while integrating both physical and psychological work environment factors for a comprehensive analysis. By providing empirical evidence on their varying impacts, the research helps organizations prioritize retention strategies. Additionally, it addresses a regional research gap and offers practical insights for policymakers and business leaders in developing economies.